Provérbios cabinda em tampas de panelas : uma análise a partir da psicolinguística da leitura e da teoria dos espaços mentais - Vitorino, César Costa (2014)
The research related to the study of Cabinda proverbs in pot lids, seeking an articulation between the Theory of Mental Spaces (TMS) and psycholinguistic theories, is an innovative area in Linguistics. This study aims at discussing how the interpretation of African proverbs used by the Cabinda, African inhabitants, is built, linking the analysis of lexical material that they support to the conception of reading in Psycholinguistics and Cognitive Linguistics perspectives, specifically in the TMS. Therefore, this study allows us to analyze some advice that cabindenses gave to their children before and after marriage, with such advice engraved on clay pot lids, where each figure shows a proverbial phrase, often containing a warning or a moral judgment. From the general objective cited above, we tried to discuss the concepts of proverbs as ethnographic objects that express cultural values of a particular community. We also sought to explain in the light of Psycholinguistics the relationship between context reader text and particularly their triple relationship in processing African proverbs. Moreover, we intended to examine the relationship between inferences and meaning production from the standpoint of the TMS, considering the need to understand cognitive processes related to language as aspects that, at the same time, constitute and are constituted by and in the social and cultural practices. The analysis will refer to six proverbs offered to the child before and after marriage, collected by Vaz (1969). Since psycholinguistics can explore relationships between proverbs and comprehension processes, we searched a link with TMS aiming at improving our understanding about the operations involved in meaning construction. The analyses of the proverbs in the light of the TMS allow us to postulate that the ability to group different mental spaces as well as the ability to create new spaces (blending) characterize cognition in human beings. Mental spaces bring partial representations of elements and relationships between them in a setting that can be perceived, understood, imagined, remembered and dreamed. According to the TMS, comprehension takes place through the creation, articulation and integration of mental spaces. In this thesis, the messages printed on the lids of pots allow us to understand that the language is always present by materializing in objects, shapes and graphic representations.